Nietzsche's Unfashionable Observations - Church, Jeffrey (Edinburgh University Press, 2022)
A critical introduction and interpretation of Nietzsche's understudied early work, the Unfashionable ObservationsThe first book-length treatment of the Observations as a wholeA companion for both students and scholars to deepen their understanding of the textContextualises the Unfashionable Observations in Nietzsche's own life, as well as in 19th-German philosophy and criticismIncludes a chronology of Nietzsche's life and work, a glossary of key terms, an index of names and subjects and a guide to further readingUnfashionable Observations - often translated as the Untimely Meditations or Thoughts Out of Season - is made up of four independent essays written between 1873 and 1876. The book remains a puzzle: what structure, principles and arguments underlie the essays?Presupposing no prior knowledge of Nietzsche or the text, Jeffrey Church sets the essays in historical and philosophical context, guides you through the text section-by-section and develops a structural overview of each essay. He reveals how the common themes of freedom, culture and genius unify the essays
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Apr 2022)
Keywords: Philosophy; PHILOSOPHY / History & Surveys / Modern